Biosynthesis of plant-specific stilbene polyketides in metabolically engineered Escherichia coli - Schmidt-Dannert Claudia; Lee Pyung C; Watts Kevin T (BMC Biotechnology, 2006)
Abstract Background Phenylpropanoids are the precursors to a range of important plant metabolites such as the cell wall constituent lignin and the secondary metabolites belonging to the flavonoid/stilbene class of compounds. The latter class of plant natural products has been shown to function in a wide range of biological activities. During the last few years an increasing number of health benefits have been associated with these compounds. In particular, they demonstrate potent antioxidant activity and the ability to selectively inhibit certain tyrosine kinases. Biosynthesis of many medicinally important plant secondary metabolites, including stilbenes, is frequently not very well understood and under tight spatial and temporal control, limiting their availability from plant sources. As an alternative, we sought to develop an approach for the biosynthesis of diverse stilbenes by engineered recombinant microbial cells. Results A pathway for stilbene biosynthesis was constructed in Escherichia coli with 4-coumaroyl CoA ligase 1 4CL1) from Arabidopsis thaliana and stilbene synthase (STS) cloned from Arachis hypogaea. E. coli cultures expressing these enzymes together converted the phenylpropionic acid precursor 4-coumaric acid, added to the growth medium, to the stilbene resveratrol (>100 mg/L). Caffeic acid, added in the same way, resulted in the production of the expected dihydroxylated stilbene, piceatannol (>10 mg/L). Ferulic acid, however, was not converted to the expected stilbene product, isorhapontigenin. Substitution of 4CL1 with a homologous enzyme, 4CL4, with a preference for ferulic acid over 4-coumaric acid, had no effect on the conversion of ferulic acid. Accumulation of tri- and tetraketide lactones from ferulic acid, regardless of the CoA-ligase expressed in E. coli, suggests that STS cannot properly accommodate and fold the tetraketide intermediate to the corresponding stilbene structure. Conclusion Phenylpropionic acids, such as 4-coumaric acid and caffeic acid, can be efficiently converted to stilbene compounds by recombinant E. coli cells expressing plant biosynthetic genes. Optimization of precursor conversion and cyclization of the bulky ferulic acid precursor by host metabolic engineering and protein engineering may afford the synthesis of even more structurally diverse stilbene compounds.